2017
DOI: 10.1002/crat.201600373
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation formation in heavily As‐doped Czochralski grown silicon

Abstract: During the growth of <100>-oriented, heavily n-type doped silicon crystals by the Czochralski method dislocation formation occurs frequently, leading to a reduction of the crystal yield. Up to now, it is not clear where and why the dislocations form. Therefore, heavily As-doped crystals were studied in this work in more detail by means of X-ray topography (XRT) and synchrotron X-ray topography (SXRT). From the data obtained it is concluded that dislocations form during growth of the top cone of the crystals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…1 shows such a case of a morphologically unstable interface, but from the end cone of a heavily P-doped Si CZ crystal. However, according to our previous study [11] on heavily As-doped crystals, in almost all cases, when dislocation formation occurred during growth of the top cone, no characteristic features of a simultaneously occurring morphological instability due to constitutional supercooling were observed. From these investigations by x-ray topography it was concluded that the cause of the dislocations is most likely in the vicinity of the so-called growth ridges of the CZ crystal, where the growth of {111} edge facets occurs [11].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…1 shows such a case of a morphologically unstable interface, but from the end cone of a heavily P-doped Si CZ crystal. However, according to our previous study [11] on heavily As-doped crystals, in almost all cases, when dislocation formation occurred during growth of the top cone, no characteristic features of a simultaneously occurring morphological instability due to constitutional supercooling were observed. From these investigations by x-ray topography it was concluded that the cause of the dislocations is most likely in the vicinity of the so-called growth ridges of the CZ crystal, where the growth of {111} edge facets occurs [11].…”
Section: Introductionmentioning
confidence: 60%
“…It was statistically observed that the dislocations form more frequently during the growth of heavily n-type doped crystals (>1x10 19 dopants/cm 3 ) than during the growth of heavily p-type or not heavily doped silicon [6][7][8][9][10]. Furthermore, it was found that dislocation formation in such heavily n-type doped Si crystals takes place more often during the growth stage of the top cone [11] and also its shape affects the risk for dislocation generation [12; 13]: The risk grows with increasing taper angle of the top cone.…”
Section: Introductionmentioning
confidence: 96%
“…These instabilities influence the growth kinetics of the growth ridges at the crystal periphery which consist of the so‐called (111) edge facets. As a result of these instabilities dislocations are formed in the vicinity of the border between the non‐facetted and facetted solid–liquid interface . Based on these finding the industrial Cz process for growing heavily n‐doped silicon can be optimized.…”
Section: Development Of Industrial Singe Crystal Melt Growth Technolomentioning
confidence: 99%
“…The reason may be that the driving force of growth was too large during shouldering, which made the spontaneous nucleation of different crystal lattice structure with the seed. Thus, polycrystalline was forming [26][27] , as shown in the raised part in Fig. 4(a).…”
Section: Design and Optimization Of Thermal Fieldmentioning
confidence: 99%